Progressive episodes of recurrent syncope due to postural orthostatic tachycardia syndrome truncated by paroxetine: a case report - Liang, Hai; Liang, Chen; Chen, Lihua; Fang, Jiayang; Yi, Yongxin; Gao, Yidong; Huang, Xiang; Chen, Xi; Liu, Ting; Pan, Wei; Yin, Lufeng (Frontiers in Psychiatry, 2025)
Postural orthostatic tachycardia syndrome (POTS) is characterized by an increased heart rate upon standing, resulting from abnormal autonomic responses that trigger symptoms when transitioning to an upright position. This syndrome predominantly manifests in late adolescence and early adulthood, with a higher prevalence observed in women. It is commonly triggered by viral infections, pregnancy, surgical procedures, or significant psychological stress. The condition presents with a wide range of symptoms, and the precise etiology of which remains unidentified. A 17-year-old woman with recurrent syncope was admitted to the hospital multiple times. Symptoms resolved rapidly following the initiation of paroxetine, a selective serotonin reuptake inhibitor (SSRI). Preliminary analysis indicated a potential shared pathophysiological basis between POTS and anxiety disorders, with norepinephrine transporter proteins emerging as a significant therapeutic target for both conditions.